Influence of Dye Adsorbtion Time on TiO2 Dye-Sensitized Solar Cell with Krokot Extract (Portulaca Oleracea. L) as A Natural Sensitizer. - Didik Krisdiyanto; Siti Khuzaifah; Khamidinal Khamidinal; Endaruji Sedyadi (Chemistry Department, The University of Brawijaya, 2015)
Dye sensitized solar cells (DSSC) photoelectrodes were fabricated using titanium oxide (TiO2) and sensitized with the krokot extract dye. This study investigated the effect of dye adsorbtion time to an efficiency of the solar cells. The fabrication cells immersed with krokot extract dye for 1, 8 and 26 hours. The photochemical performance of the DSSC showed that the open circuit voltage (Voc) were 0.33, 0.036 and 0.27 V with short photocurrent density (Isc) 8.00 x 10-5, 6.80 x 10-7 and 3.10 x 10-4. The photo-to-electric conversion efficiency of the DSSC reached 4.63 x 10-3 % for 26 hours adsorbtion time.